From Reverence to Routine: Rethinking Oath Taking in Trial Courts by Muslims - Umar, Muhammad; Azeem, Hafiz Muhammad; Mubashar Tariq, Mubashar Tariq (Al-Amīr Research Journal for Islamic Studies, 2024)
In the sacred court rooms for justice, oaths were once expressed with respect and deep deference for religion. They were sufficient evidence in a case. Yet, in the modern culture of courts proceedings in Pakistan, this sacred exercise has become a mere formality. It has lost its true worth. During trial proceedings oaths are now sworn informally and often, frivolously, without thinking about their moral, social and religious consequences. This paper aims to highlight the place of oaths in Islamic legal jurisprudence. Through analysis of the injunctions laid down by the Quran, Sunnah, this work explains the real role of oaths in a trial proceeding. Furthermore, this research aims to enhance the awareness regarding the reverential status of oaths among all stakeholders of justice system in Pakistan, such as police officers, prosecutors, judges, and private litigants. This paper will provide them essential reasoning and the necessary knowledge to restore the proper place and weightage that an oath deserves in trials. To build a just and peaceful society, where citizens have firm confidence in courts, it is indispensable to restore the sanctity of oaths within our justice system and curb the menace of false oaths. Keywords: Oaths, False Oaths, the Oaths Act, 1873, Oaths in Islam.